Una aproximación desde el uso pedagógico de ciertas polémicas públicas: proceso de paz con las FARC-EP - Hernández Guzmán, Claudia Marcela (Pedagogía y Saberes, 2021)
Throughout the recent peace process between the Colombian Government and farc-ep, various discursive situations acquired a controversial or polemical character. These situations, in light of the plebiscite held in 2016 to endorse the Final Agreement, seemed counterproductive to the positive outcome of the process. The purpose of this article is to analyze the pedagogical use that the Office of the High Commissioner for Peace gave to certain scenarios of public polemics, which took on a significant media force within the framework of Peace Pedagogy. Based on the selection of audiovisual and written material, we propose a reconstruction of certain discourses that were opposed to the peace process and of the counterarguments developed by the Colombian government, in order to highlight possible relations between the “pedagogic dispositive” and the public polemics. Finally, we point out that public polemics can be understood in terms of their pedagogical potential, which allow the opening of argumentation scenarios and a consequent resignification of knowledge and (re)configuration of identities.